PERSEPSI MASYARAKAT KECAMATAN DETUKELI TERHADAP KONSEP PELESTARIAN HUTAN WISATA AMPUPU KEBESANI BERBASIS KEARIFAN LOKAL - Sagajoka, Estherlina; Nona, Reyna Virginia; Valentin, Marselina (ANALISIS, 2022)
The purpose of this study was to determine the perception of the people of Detukeli District about the Preservation and Development of the Ampupu Tourism Forest in Kebesani Village. Based on local wisdom, using a qualitative descriptive method. The population in this study is the people of Detukeli District, with a sample of 160 respondents consisting of: traditional leaders (mosalaki), religious leaders, marginalized communities (anakalo fai walu,) policy makers, politicians, and academics who come from the Detukeli District. The results showed that 47.2% of respondents agreed with the concept of conservation and development of tourism forest based on local wisdom, but it has not been applied properly and correctly among the community, 26.1% of respondents agreed and had applied it, and respondents who agreed to this statement were dominated by academics, 20.0% of respondents disagree and do not understand, Then 6.7% of respondents have understood the concept of forest tourism preservation but do not agree with the concept offered because they do not understand, so the concept of forest conservation and development based on local wisdom needs to be socialized properly , true and sustainable to all citizens. The recommendations given are: 1) Socialization must be provided by competent parties on the preservation and development of sustainable forests based on local wisdom, 2). Socialization must accommodate/cooperate with traditional stakeholders, religious leaders, policy makers at both the sub-district and village levels. Politicians and academics, 3) The development of forest conservation into a tourist destination based on local wisdom needs to be paid special attention to the myths and culture of the indigenous people of Kebesani Village, where the development of the Ampupu Forest as a new tourist destination is maintained and preserved according to the "Pire-Bhisagia" culture and is expected to provide added value for economic activities for the village community of Kebesani and its surroundings in accordance with sustainable development.